Seed pre-sowing treatments and essential trace elements application effects on wheat performance - Janmohammadi, Mohsen (Acta agriculturae Slovenica, 2023)
Current study was conducted to evaluate the ef-fects of different seed priming and foliar spray of micronutrients on bread wheat performance in semi-arid region in Northwest of Iran. Pre-sowing treatments were S1: no pre-sowing treat-ment (intact seeds), S2: hydro-priming, S3: bio-priming (seed inoculation with plant promoting rhizobacteria consortium: Azotobacter chroococcum + Azospirillum lipoferum), S4: mi-cronutrient seed priming and foliar feeding include, check (0): distilled water spray, Fe: foliar spray of iron, Zn: foliar spray of zinc. All seed priming treatments significantly increased plant height, tiller number, canopy width, total biomass, spike mass, seed number per spike and seed yield compared to intact seeds. A brief comparison of the effect of seed priming and fertilizer treatments showed that the effects of priming treatments on im-proving growth and seed yield was more obvious than fertilizer treatments. The greatest increase in seed yield and yield com-ponents was recorded for plants grown from bio-fortified seeds by essential trace elements. However, comparison of fertilizer treatments showed that growth parameters were significantly affected by Zn application. From the present study, it may be concluded that combined seed priming through pre-sowing hy-dration, soaking in micronutrients and microbial inoculation is useful to enhance wheat production and agricultural sustain-ability for smallholder farmers in semi-arid region.
Keywords: bio-priming; hydro-priming; nutrient priming; obdelava pred setvijo; predtretiranje s hranili; pridelek semen; seed yield; seme